2017
DOI: 10.1109/jsyst.2015.2496293
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions on the State of the Art in Verification and Validation in Cyber-Physical Systems

Abstract: It is widely held that debugging cyber-physical systems (CPS) is challenging; many strongly held beliefs exist regarding how CPS are currently debugged and tested and the suitability of various techniques. For instance, dissenting opinions exist as to whether formal methods (including static analysis, theorem proving, and model checking) are appropriate in CPS verification and validation. Simulation tools and simulation-based testing are also often considered insufficient for CPS. Many "experts" posit that hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 84 publications
0
56
0
Order By: Relevance
“…Lots of testing and formal methods have been proposed which involve from consistency verification [76] to dynamic logic validation [77], and the targets include circuits, chips, network, software, systems and requirements, etc. [76][77][78][79]. Sara et al analyzed the need of multiple levels testing on CPS and made the state-of-the-art survey on testing methods and conclude the challenges in CPS testing [80].…”
Section: Approaches On the Correctness Vandv Of Self-adapting Cpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lots of testing and formal methods have been proposed which involve from consistency verification [76] to dynamic logic validation [77], and the targets include circuits, chips, network, software, systems and requirements, etc. [76][77][78][79]. Sara et al analyzed the need of multiple levels testing on CPS and made the state-of-the-art survey on testing methods and conclude the challenges in CPS testing [80].…”
Section: Approaches On the Correctness Vandv Of Self-adapting Cpsmentioning
confidence: 99%
“…E.g. worstcase execution time (WCET) analysis [104], perceptions scheduling V&V [79]. A general model of mixed-criticality recurrent real-time tasks was proposed, and the analysis model took WCET, relative deadline, and period into account at two criticality levels [105].…”
Section: Vandv On Real-time Schedulabilitymentioning
confidence: 99%
“…Compared with the growth of the domain, verification and validation of CPS lags far behind [32]. The state of the practice in debugging CPS generally entails a combination of simulation and in situ debugging.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis concluded that, although simulation-centric tools are indispensable for rapid prototyping, design, and debugging, they are limited in providing correctness guarantees. State of the art formal methods tools, including static analysis, theorem proving, and model checking, are insufficient in tackling the challenges in CPS verification and validation [32]. Other verification techniques, including model-based testing [11] and simulation [16] have high learning curves, impractical development costs, and scalability issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation